How do university workers eat at the workplace?. Issue 2 (12th March 2018) - Lima, João; Costa, Sofia; Rocha, Ada
Abstract : Purpose: Food consumed at work can be brought from home or taken in private or university restaurants. Knowing the contribution of food consumption in the workplace allows for the identification of bad practices to modulate food availability in the work environment and raise consumer awareness for a more balanced food intake. This paper aims to characterize food consumption and to determine the contribution of food consumption at the workplace to daily food intake of employees of the University of Porto (UP). Design/methodology/approach: A cross-sectional observational study was conducted. The project was approved by Ethical Commission of the UP. The principles of Helsínquia Declaration were respected and the workers under examine accept to participate in the study, through an inform consent. Data were obtained through the application of a self-administrated questionnaire and through the application of a questionnaire including a 24 h recall. There were assessed 513 individuals randomly selected, and the majority of them were women. Findings: In total, 92.8 per cent of them preferred to have meals at the workplace that contributed to about 39.6 per cent of the daily energy intake. Reported food consumption at the workplace contributed about 42.6 per cent of carbohydrates, 39.4 per cent of total fat and 36.8 per cent of proteins for daily intake. A low intake of water (39.2 per cent of whole ingestion) and a huge amount and contribution of the workplace (48.4 per cent) to daily sugar intake was observed. Higher nutritional intake was observed for women ( p < 0.05). The energy contribution of meals at the workplace is in accordance with recommendations, except for breakfast, that is below. Originality/value: This work allows to characterize food habits of university employees at the workplace and the identification of the contribution of meals eaten at the workplace for daily energy and nutritional intake. These data allow to modulate food availability in the work environment and raise consumer awareness for a more balanced food intake.